Traduction domestique : un marché glocal pour la poésie en espagnol - Azucena G. Blanco; Erika Martínez (Caravelle)
In recent years, the discourse of comparative literature has been transformed by the discussion about relations between literature, market and globalization. Theorists like D. Damrosch (World Literature), G. Spivak (Planetariety), Pascale Casanova (The World Language) or L. Venuti (translation and globalization), among others, have responded from different perspectives to this debate. Our purpose here is to analyze inside this theoretical framework and from the periphery (parochialism) an example of literature and translation market as resistance/domestication to the homogenizing trend of globalization, that we have called “domestic translation”. Dialectal poetry translation in Spanish allows us to go into a fundamental case of literary movements in the market for what is called glocalization as an effective alternative to globalization.